Dynamic remote monitoring system for plant root growth and water consumption - Wenting, Han; Yutu, Ju; Pute, Wu; Gerong, Dang; Junfeng, Nie; Ooi, Su Ki (International Journal of Agricultural and Biological Engineering, 2013)
In order to improve the level of multi-functional and automatic observation of crop root system growth, a soil column monitoring system was designed to facilitate in situ dynamic monitoring of root growth and water consumption. The system consists of 20 plastic tubular backfill soil columns, each with an inner diameter of 32 cm and height of 300 cm. The crops were planted at the top of the soil column with the surrounding leveled with the ground surface and the site is in a greenhouse. The underground portion of the soil column contains small round windows on the tube through which root growth can be monitored, roots can be pruned and soil samples can be obtained. A multiport serial weighing system was designed and placed at the base of the soil column. Twenty electronic balances were connected to the personal computer through three CP-168U multiport serial cards and RS-232 serial cables. The host software was developed on the browser/server (Browser/Server), and data collection and remote data transmission and data sharing were implemented using the Java programming language and applying Internet data transmission technology and Web application technology. System tests showed a relatively good stability and real-time capability, and with accuracy up to 50 g and the evapotranspiration of each soil column was 0.25-0.65 kg per day. The root-system observation system developed in this study surpassed the traditional method of root-digging sampling and thus provided an alternative that could be used to automatically monitor the root system growth status.